Game-Boards and Gaming-Pieces in Funerary Contexts in the Northern European Iron Age - Whittaker, Helène (Nordlit, 2006)
Gaming-pieces, dice, and game-boards are found in connection with burials at various times and places from an early date. For instance, in Egypt there was a clear association between the game known as Senet and burials from the time of the Old Kingdom (Pusch 1979; Piccione 1984). Dice are not uncommonly found in Greek, Etruscan, and Roman tombs (Vermeule 1979, 80; Pallottino 1955, fig. 95; Egidi 1983). It can reasonably be assumed that the playing of board games was seen as a pleasurable pastime which one could hopefully continue to pursue in the Afterlife. However, it can in some cases be argued that gaming equipment in burial contexts was related to the social status of the deceased or to religious beliefs and therefore had a more complex significance. In this article I will look at the occurrence of gaming-pieces, dice, and game-boards in burials in the northern European Iron Age.